(untitled) (Scientific journal of the Fergana State University, 2023)
This article talks about the traditionality of the image of clothes related to the wedding ceremony, coming as a stable symbolic image. In Uzbek folklore, clothes are connected with the ideas of love, family, children, fertility, household life in real and symbolic terms. Also, every folk song reflects the social lifestyle. Often, in ritual songs, objects and things specific to old and new marriages are compared. The songs reflect the magical power of the world, belief in it, and the rituals associated with it. The names of clothes, which are an integral part of the lexical wealth of the national language, come not only with artistic expression, but also prove the existence of their naming features. Also, auxiliary parts such as skirts, belts and collars have their own symbolic meaning. The expressed a specific artistic and aesthetic task. The types of fabrics shown in the dressesworn by the bride and groom during the marriage ceremony also show the class representative of the lyrical hero in the song. In particular, the importance of clothing images in the expression of the love of the sexes, family, children, friends and parents in folk lyrics has been highlighted through historical-cultural and comparative-analytical methods.